Methanol Production from Biogas-derived Syngas - Zhang Huili; Kou Yibing; Baeyens Jan; Yang Miao; Deng Yimin (E3S Web of Conferences, 2025)
"Green" hydrogen must gradually replace fossil fuel-based H2. The anaerobic digestion (AD) of sewage sludge or agro-industrial waste yields a CH4/CO2 biogas and a NH4+ digestate. Three ways to produce H2 can be applied: (1) the Dry Reforming of CH4, and CO2, DRM (from biogas); (2) the Catalytic CH4 Decomposition, CDM (from biogas after CO2 capture) and (3) the Catalytic Ammonia Decomposition (CDA, from digestate). DRM produces the ideal syngas at 700 °C and for a 50-50vol% CH4/CO2 biogas. CDM with a selected catalyst produced 95% H2. The ammonia-rich digestate was stripped and NH3 was catalytically decomposed into H2 and N2 at 650 °C. Considering the well known difficulties of storing H2, a conversion of syngas to methanol was studied for a wastewater treatment plant (WWTP) with A.D. of 300,000 person equivalent (PE) is examined; and simulated using Aspen Plus®. This AD process generates a daily feed rate of 4,485 m3 CH4, 2,415 m3 CO2 and 320 kg NH3, resulting in a CH3OH production of 183 kg/hr. The additional CDA H2 flow (631 m3/day) is not needed in the methanol production and can be co)fired in the Combined Heat and Power (CHP) normally associated with AD. CDA will produce more H2 if NH3-richer manure would be digested.